Traffic-related pollutants in urban snow : Concentrations, size fractionation, and release with snowmelt - Vijayan, Arya (Luleå tekniska universitet, Arkitektur och vatten, 2023)
In urban areas with seasonal snow, traffic-related pollutants such as solid particles, metals, chloride, organic pollutants, and microplastics (MPs) can be temporarily stored in snowbanks along roads and streets. When the snow melts, it releases the accumulated pollutants and the resulting snowmelt with diverse pollutants may partly infiltrate into the ground, or enter storm sewers and eventually be discharged into, and impact on, the receiving waters. To address the resulting environmental concerns, it is important to gain a more comprehensive understanding of (i) occurrence, distribution, and temporal variation of conventional (TSS, Cu, Zn, Pb, Cd, chloride and PAHs) as well as emerging pollutants (Tire and Road Wear Particles (T&RWPs), Platinum Group Elements (PGEs), tungsten (W) and antimony (Sb)) in urban snow, (ii) size fractionation of pollutants in snow, (iii) behaviour of pollutants during snow melting, and (iv) influence of various snow sampling strategies on estimating pollutant loads in snow. Therefore, these four points form the focus of this doctoral thesis. The work presented in the thesis includes a literature review of metal pollution in urban snow, field sampling of urban roadside snowbanks and snow storage piles, and laboratory-scale snow melting experiments. The field sampling included snow sampling surveys at three locations in Sweden – Frihamnen (one of the ports of Stockholm), and Luleå and Umeå municipalities in Northern Sweden, and served for studies of variations in snow quality in terms of solids, metals, chloride, PAHs and MPs. Some of the field samples were also used in laboratory-scale snow melting experiments to advance the understanding of the fate of pollutants during the snow melting process. A literature survey identified Zn, Cu, Pb, Cd and Ni as the metals most frequently studied in urban snow, while Sb, W and PGEs in urban snow were seldom studied, and consequently were designated here as ‘emerging pollutants’ in urban snow. These pollutant concentrations in the analysed ...